Gender and Its Implications for Cardiothoracic Perioperative Care and Anesthesia - Schopper, Miriam; Irnich, Dominik (The Thoracic and Cardiovascular Surgeon, 2013)
Differences in gender can influence perioperative outcome, with men and women being differently affected by adverse events in the perioperative period. Differences relating to specific drug effects, comorbidities and outcomes after anesthesia or intensive care have been demonstrated. There is a gender bias in diagnosis and therapy. While knowledge regarding this field is still growing, certain aspects have already been integrated into clinical practice (prevention of postoperative nausea and vomiting, target-controlled infusion, male-only policy with production of blood products). There is a need to study the influence of gender, age, and race on perioperative outcome to optimize treatment and move toward more individualized therapy. This article highlights already identified differences and discusses potential underlying mechanisms.
Keywords: sex; bias; treatment outcome; chronic pain; sex steroid hormones